From scientific exploitation to individual memorialization: Evolving attitudes towards research on Nazi victims’ bodies - Czech, Herwig; Weindling, Paul; Druml, Christiane (Bioethics, 2021)
During the Third Reich, state‐sponsored violence was linked to scientific research on many levels. Prisoners were used as involuntary subjects for medical experiments, and body parts from victims were used in anatomy and neuropathology on a massive scale. In many cases, such specimens remained in scientific collections and were used until long after the war. International bioethics, for a long time, had little to say on the issue. Since the late 1980s, with a renewed interest in the Holocaust and other Nazi crimes, a consensus has increasingly taken hold that research on human tissues and body parts from the Nazi era is inadmissible, and that such specimens should be removed from scientific collections and buried. The question of what to do with scientific data obtained from these sources has not received adequate attention, however, and remains unsolved. This paper traces the history of debates about the ethical implications of using human tissue or body parts from the Nazi period for scientific purposes, primarily in the fields of anatomy and neuropathology. It also examines how this issue, from after the war until today, influenced the establishment of legal and bioethical norms on the use of human remains from morally tainted sources, with a particular emphasis on Germany and Austria. It is argued that the use of such specimens and of data derived from them is unethical not only because of potential harms to posthumous rights of the victims, but also because such use constitutes a moral harm to society at large.